The Political Dominance of the Bugis in the Coastal Region of Indonesia from the 17th Century to the 19th Century - A. Alamsyah (Journal of Maritime Studies and National Integration, 2022)
The inter-royal conflict and the control of Makassar by the VOC in South Sulawesi in the 16th to 17th centuries had a major impact on the socio-political development of the Bugis. This condition made the Bugis make a large-scale migration. Bugis local culture also spread to various regions along with the migration process. The control of Makassar port by the Dutch colonial made the Bugis feel driven from Makassar. In this migration process, there are groups that choose to trade. While the rest settled outside Sulawesi. The Bugis became nomads in various regions of the archipelago, mostly living in coastal areas, which later built up political power. In their development, they became successful nomads, especially in the political field, especially in some coastal areas, such as Bali, West Kalimantan, East Kalimantan, South Kalimantan, Sumbawa, and in the Malay Peninsula. The Bugis managed to establish good communication with the local population. They are also a highly respected community group in overseas territories